Covid-19 and Mental Health: Could Visual Art Exposure Help? - Gallo, Laura M. H.; Giampietro, Vincent; Zunszain, Patricia A.; Tan, Kai Syng (Frontiers in Psychology, 2021)
A worldwidemental health crisis is expected, as millions worldwide fear death and disease while being forced into repeated isolation. Thus, there is a need for new proactive approaches to improve mental resilience and prevent mental health conditions. Since the 1990s, art has emerged as an alternative mental health therapy in the United States and Europe, becoming part of the social care agenda. This article focuses on how visual esthetic experiences can create similar patterns of neuronal activity as those observed when the reward system is activated. The activation of the reward structures could have a stress buffering effect, given the interdependence observed between the reward and stress systems. Therefore, could visual esthetic experiences stimulate mental resilience? And if this were the case, could art-based interventions be offered for mental health in the context of COVID-19 and beyond?